Parent Isotopic and Elemental Contributing Factors to Minimize Nuclear Radiological Responses and Optimize Material Composition. (2nd December 2017) - Tadepalli, Sai Chaitanya; Kanth, Priti; Subhash, P. V.
Abstract: The next generation nuclear facilities like Gen-IV fission reactors and fusion plasma will have a huge amount of activated waste production and resulting harmful consequences in terms of radioactive responses such as activity, decay heat, and dose. It is imperative to understand and quantify the impact of individual parent elements or isotopes in the material on major radiological responses. Such quantification serves as an impact indicator. This paper attempts to develop a method to aid this quantification that would eventually offer a complete material activation analysis. Here, we begin by presenting the mathematical formulation to account for the contribution of the parent constituents of any irradiated material toward the radiological responses directly, defined as the contributing factor (CF). The method is easily adaptable to other activation solvers and provides the user with CFs of parents that highlight the individual importance of the constituents. These factors can be used to determine the impact of elements on radiological quantities and how much tailoring of these elements will affect the radiological response of the material. All these can be done in a single run of the code, developed as an aid to activation solvers. Moreover, improved response of the modified material composition after reducing harmful parents can be directly calculated using the derived CFs without rerunning the solver. Thus, an optimized composition of the material either isotopically or elementwise can be easily obtained. A few examples highlighting the application of this technique and its importance are provided at the end.